Standing in another man's grave - Rankin, Ian. (New York : Reagan Arthur Books/Little, Brown and Company, 2013)
Two Scottish detectives investigate the disappearance of a hitchhiking teenage girl, their only clue a photo sent from the missing girl's cell phone.
"A Reagan Arthur book."
Keywords: Missing persons -- Fiction; Cold cases (Criminal investigation) -- Fiction; Detective and mystery stories; Mystery fiction